AN ANALYSIS OF STUDENTS’ LEARNING STYLE IN LEARNING ENGLISH AT EIGHTH GRADE OF SMP N 1 TEMBILAHAN HULU - Sipa Sapira; Melda Yeni; Felci Tria Sauhana (Program Studi Pendidikan Bahasa Inggris, 2022)
This study was a descriptive study that aimed to determine students' learning styles in learning English. The population of this study was the eighth grade students of SMP Negeri 1 Tembilahan Hulu using random sampling technique. The data collection method used is a questionnaire. The results of this study of learning style tendencies indicated that the learning style with the number of respondents was 30 students with average score of 93.38 into the enough category. In addition, it was found that learning outcomes with visual learning styles were included in the “Enough category” with an average score of 95.13, auditory learning styles were in the “Good category” with average score of 104, and kinesthetic learning styles were included in the “Enough category” with average score of 81. Thus the learning style applied in the eighth grade was more likely to be an auditory learning style with the number of respondents being 30 students and obtaining learning outcomes in a good category with an average value of 104. From these results, it can be concluded that the eight SMP N 1 Tembilahan Hulu pay less attention to their learning style. This could be one of the reasons why some of the scores of their kinesthetic learning style showed less and bad categories. Besides that, it could be a reminder for teachers to be able to prepare strategies in growing student learning styles that could help to improve students in learning English. This study was a descriptive study that aimed to determine students' learning styles in learning English. The population of this study was the eighth grade students of SMP Negeri 1 Tembilahan Hulu using random sampling technique. The data collection method used is a questionnaire. The results of this study of learning style tendencies indicated that the learning style with the number of respondents was 30 students with average score of 93.38 into the enough category. In addition, it was found that learning outcomes with visual learning styles were included in the “Enough category” with average score of 95.13, auditory learning styles were in the “Good category” with average score of 104, and kinesthetic learning styles were included in the “Enough category” with average score of 81. Thus the learning style applied in the eighth grade was more likely to be an auditory learning style with the number of respondents being 30 students and obtaining learning outcomes in a good category with an average value of 104. From these results, it can be concluded that the eight SMP N 1 Tembilahan Hulu pay less attention to their learning style. This could be one of the reasons why some of the scores of their kinesthetic learning style showed less and bad categories. Besides that, it could be a reminder for teachers to be able to prepare strategies in growing student learning styles that could help to improve students in learning English.